2023
DOI: 10.1111/caim.12558
|View full text |Cite
|
Sign up to set email alerts
|

Where business model innovation comes from and where it goes: A bibliometric review

Abstract: Business model innovation (BMI) has been evolving as a burgeoning topic in academia and business practice for over two decades. In recent years, knowledge production within the BMI field is accelerating at a tremendous rate, making it hard to keep up with the state of the art. Given its broad literature coverage and the systematic and reproducible process of applying statistical and quantitative techniques, the bibliometric review can complement existing structured literature reviews by providing a holistic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 114 publications
0
17
0
Order By: Relevance
“…This aligns with what Urbano, Turro, Wright, and Zahra (2022) have recently highlighted that, in contrast to the literature on early-stage entrepreneurship in which the fundamental importance of opportunity discovery skills like entrepreneurial alertness has been extensively examined, we still have surprisingly little knowledge on the role of such strategic opportunity discovery skills in firms' innovation management practices (Roundy et al, 2018;Tang, Baron, & Yu, 2021). This study's findings contribute to the innovation management literature on BMI, and particularly to the growing literature on the cognitive perspective on BMI, by offering new empirical knowledge on the critical strategic role of business owners' entrepreneurial alertness for BMI during severe crises (Andersen et al, 2022;Zhang et al, 2023;Zhao et al, 2021). Next to this, our robust results add to the literature on corporate venturing practices by revealing that BMI functions as a mediating mechanism that can significantly lead to the creation of a new ICV, which can be used as a tool for organizations to implement a new business model for the firm (Bachmann & Jodlbauer, 2023;Roundy et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…This aligns with what Urbano, Turro, Wright, and Zahra (2022) have recently highlighted that, in contrast to the literature on early-stage entrepreneurship in which the fundamental importance of opportunity discovery skills like entrepreneurial alertness has been extensively examined, we still have surprisingly little knowledge on the role of such strategic opportunity discovery skills in firms' innovation management practices (Roundy et al, 2018;Tang, Baron, & Yu, 2021). This study's findings contribute to the innovation management literature on BMI, and particularly to the growing literature on the cognitive perspective on BMI, by offering new empirical knowledge on the critical strategic role of business owners' entrepreneurial alertness for BMI during severe crises (Andersen et al, 2022;Zhang et al, 2023;Zhao et al, 2021). Next to this, our robust results add to the literature on corporate venturing practices by revealing that BMI functions as a mediating mechanism that can significantly lead to the creation of a new ICV, which can be used as a tool for organizations to implement a new business model for the firm (Bachmann & Jodlbauer, 2023;Roundy et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…While empirical insights remain sparse, scholars have suggested that engaging in BMI, particularly for SMEs, can be an especially potent strategic response to address extreme crises to remain viable (Breier et al, 2021;Hashemi, Rajabi, & Brashear-Alejandro, 2022;Kraus et al, 2020;Zhang et al, 2023). Research increasingly shows that the ability to innovate the firm's business model can particularly determine SMEs' survival and success (i.e., firm performance), which becomes even more critical during severe crises like COVID-19 (Andersen et al, 2022).…”
Section: Entrepreneurial Alertness and Bmi During Severe Crisesmentioning
confidence: 99%
See 3 more Smart Citations